Pengendalian Persediaan Barang Dagang Untuk Peningkatan Kualitas Operasional Pada Indomaret Sudirman Selat Baru Bengkalis - Nur Anita; Umul Khairiah (Universitas Sahid Surakarta, 2022)
The goal of this study was to determine Indomaret Sudirman Selat Baru Bengkalis's internal inventory control. In this study, a descriptive method with a qualitative approach is used, with interviews, documentation, and observation as methods for data collection. The study's findings suggest that inventory internal control has been properly implemented. This is proved by the division of tasks, the delegation of authority and responsibility in accordance with the employees' duties and functions. Procedures for attempting to control merchandise inventory at Indomaret Sudirman Selat Baru Bengkalis are carried out in accordance with company operational standards, both during the ordering, receiving, storing, and sending of goods, and must be pre-approved by authorized store officials.“This research can be used as a reference for future studies,”add insight and knowledge to readers, and provide additional insight to business people on good inventory management in large companies in order to improve the quality of company operations in order to achieve profits for long-term sustainability.